The Sioux [book with audioplayer] - Sneve, Virginia Driving Hawk (Sneve, Virginia Driving Hawk. First Americans book., 2025)
Learn about the Sioux creation story, life in the village as a kid, the importance of their feathered headdresses, and more. This updated edition provides the most up to date and accurate information on the Sioux people of past and present. The back of the book includes a section on Sioux life today, proper names for all of the Sioux tribes, and an excerpt from the Lakota pipe ceremony.